2007
DOI: 10.1111/j.1748-5967.2007.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the chelicera in the spider Nephila clavata

Abstract: The fine structural characteristics of the biting apparatus in the orb‐web spider Nephila clavata were studied using scanning electron microscopy. The main biting apparatuses of spiders are the chelicerae and cheliceral fangs in the cephalothorax. The chelicera of N. clavata is that of the jack‐knife (folding knife) type, which is composed of two segments, and has a labidognathous form that moves at right angles to the body axis. Each chelicera bears a hinged fang that folds into a cheliceral groove. The tips … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Among their several functions such as those in cleaning behaviour and the widening and opening of the egg sac to release the spiderlings, the mechanically most demanding function of the cheliceral fangs is to puncture the cuticle of prey insects in order to inject the venom 21 22 23 . Spider fangs typically are a few millimetres long, of conical shape, hollow and curved 24 25 . The fang is essentially made of two elements, chitin fibres embedded in a protein-rich matrix, which together form a stiff light-weight structure 26 .…”
mentioning
confidence: 99%
“…Among their several functions such as those in cleaning behaviour and the widening and opening of the egg sac to release the spiderlings, the mechanically most demanding function of the cheliceral fangs is to puncture the cuticle of prey insects in order to inject the venom 21 22 23 . Spider fangs typically are a few millimetres long, of conical shape, hollow and curved 24 25 . The fang is essentially made of two elements, chitin fibres embedded in a protein-rich matrix, which together form a stiff light-weight structure 26 .…”
mentioning
confidence: 99%
“…Notably, we found that, not only were the venom glands absent, but the opening of the venom duct in the tip of the fangs was also not visible, suggesting a complete loss of the venom apparatus. Nevertheless, we observed the presence of small pores on the fangs, which seem commonly found in spiders (Moon and Yu 2007), but whose function remains unknown. In contrast to the histology results, transcriptomics analysis revealed the expression of genes related to venom components in the prosoma, where venom glands are typically found.…”
Section: Discussionmentioning
confidence: 66%
“…2B). Similar small cuticular pits have been observed at the fang's tip of the orb-web spider Nephila clavata, although their function remains unknown (Moon and Yu 2007).…”
Section: Scanning Electron Microscopymentioning
confidence: 56%
“…The wasp spider carries ventral cheliceral teeth that accommodate the fang when the venom delivery system is in its resting position. Cheliceral teeth are found in several spider lineages and enable a secure grip on prey [ 48 ]. They are also used to mechanically break up food by species that practice extraintestinal digestion, promoting liquefaction by digestive fluids [ 45 ].…”
Section: Discussionmentioning
confidence: 99%